2003
DOI: 10.1177/0091270003253349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Intrathecal Ziconotide in Chronic Pain Patients

Abstract: The pharmacokinetics and pharmacodynamics of ziconotide were assessed over a 48-hour period following intrathecal (i.t.) administration (1, 5, 7.5, or 10 micrograms) to 22 patients with chronic, nonmalignant pain. Plasma and cerebrospinal fluid (CSF) samples were obtained over a 24-hour period. Analgesic efficacy was monitored using Visual Analog Scale of Pain Intensity (VASPI) and Category Pain Relief Scores (CPRS) measurements. Pharmacokinetic (PK) parameters were calculated by noncompartmental methods. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 16 publications
1
43
1
Order By: Relevance
“…These results compare favorably with a report on LCSF PK in humans after an acute (one‐hour infusion) of ziconotide in humans (16). In that work, after one‐hour IT bolus administration of ziconotide in doses of 1–10 µg, an exponential CL was noted more than 24 hours.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results compare favorably with a report on LCSF PK in humans after an acute (one‐hour infusion) of ziconotide in humans (16). In that work, after one‐hour IT bolus administration of ziconotide in doses of 1–10 µg, an exponential CL was noted more than 24 hours.…”
Section: Discussionsupporting
confidence: 86%
“…Studies in humans also have shown that IT bolus injection or continuous infusion of ziconotide is efficacious in a variety of acute and chronic pain states (13–18) and in ameliorating spasticity secondary to spinal injury (19). Initial studies reported significant adverse effects with dose incrementation (15,20), which may have reflected an incomplete appreciation of the kinetics of redistribution of the intrathecally delivered drug.…”
Section: Introductionmentioning
confidence: 99%
“…This patient was given ziconotide by continuous, constant rate, intrathecal infusion and complete pain relief was achieved, even after the dose was lowered to 2 ng/kg hourly to alleviate the patient’s side-effects of dizziness, blurred vision, and nystagmus. Another trial evaluated the analgesic efficacy, safety, and pharmacokinetic properties of intrathecal ziconotide in patients with chronic neuropathic pain (Wermeling et al 2003). Ziconotide was infused over a 1-hour period at doses of 1, 5, 7.5, or 10 μg.…”
Section: Ziconotide: Clinical Studiesmentioning
confidence: 99%
“…Ziconotide (Prialt®) has been recently approved by the FDA for use in severe pain. However, the therapeutic index of intrathecal MVIIA is narrow and the severity of adverse side-effects appears dose-dependent (Horvath et al, 2002; Scott et al, 2002; Wermeling et al, 2003). …”
Section: Introductionmentioning
confidence: 99%